Intrahousehold Time Allocation: An Impact Evaluation of Conditional Cash Transfer Programs (2015)
This paper argues that exogenous changes in household income alter the allocation of time within the family. To examine this issue, we propose a theoretical framework that is an extension of the unitary model of intra-household time allocation where conditional cash transfers are received by the household and we test it empirically using non-parametric techniques. This allows us to study the effects of an exogenous shock, such as a conditional cash transfer program, on time allocated to various activities such as work, domestic labor, leisure, and school for children and adults. Using the exogenous change of a conditional cash transfer program in Colombia, "Familias en Accion", we find significant positive effects on work time as well as on leisure and school for children and smaller effects on adult schooling and domestic labor, which support our hypothesis. These results are crucial to fully understand other direct and indirect effects of the program.